A Pumilio Activity Sensor Reveals Bag-of-Marbles Inhibition of Pum Activity in the Drosophila Ovary. - Jang, W.; Kim, C. (Development & reproduction, 2023)
Pumilio (Pum) is an RNA-binding protein and translational repressor important to diverse biological processes. In the Drosophila ovary, Pum is expressed in female germline stem cells (GSCs), wherein it acts as an intrinsic stem cell maintenance factor via repressing target mRNAs that are as yet mostly unknown. Pum recognizes the Pum binding sequence (PBS) in the mRNA 3'UTR through its C-terminus Puf domain. Translational repression is mediated through its N-terminal domain, but the molecular mechanism remains largely unknown. We previously showed that Bag-of-marbles, a critical differentiation-promoting factor of female GSCs, physically interacts with the N-terminus of Pum. We further showed that this interaction is critical to Bam inhibition of Pum repressive action in cultured cells, but the physiological relevance was not addressed. Here we design an in vivo GFP translational reporter bearing the PBS in its 3'UTR and show that GFP expression is reduced in cells wherein Pum is known to be active. Furthermore, we demonstrate in pum mutant ovary that this GFP repression requires Pum, and also that the sensor faithfully monitors Pum activity. Finally, we show that forced expression of Bam inhibits Pum-mediated repression, validating that Bam inhibits Pum activity in vivo.